Multiple examinations indicated associations between abnormal regional homogeneity and cognitive dysfunction in major depressive disorder - Wang, Yun; Li, Xiaoling; Yan, Haohao; Zhang, Qinqin; Ou, Yangpan; Wu, Weibin; Shangguan, Webo; Chen, Wensheng; Yu, Yang; Liang, Jiaquan; Wu, Wanting; Liao, Hairong; et al. (Frontiers in Psychology, 2023)
Background This study aimed to investigate the relationships between regional neural activity and multiple related indicators in patients with major depressive disorder (MDD). Methods Forty-two patients and 42 healthy controls (HCs) were enrolled. Pearson/Spearman correlation analyses were applied to examine the associations between abnormal regional homogeneity (ReHo) and different indicators in the patients. Results Compared with HCs, patients with MDD had increased ReHo in the left inferior temporal gyrus (ITG) and decreased ReHo values in the left putamen, anterior cingulate cortex (ACC), and precentral gyrus. The ReHo of the left putamen was positively correlated with the PR interval, Repeatable Battery for the Assessment of Neuropsychological Status 4A, and Discriminant analysis (D), and negatively correlated with Ae (block) and Ae (total) in the patients. The ReHo value of the left ACC was positively correlated with the severity of depression, Stroop Color Word Test of C − 2B + 100 in reaction time, and negatively correlated with Ce (Missay) and Perseverative Responses in the patients. The ReHo of the left ITG was positively correlated with the Neuroticism scores and negatively correlated with the Lie scores in the patients. Conclusion These results suggested that the decreased ReHo of the salience network might be the underpinning of cognitive impairments in patients with MDD.